Ревизия палеоарктических видов галлиц рода Coquillettomyia Felt (Diptera, Cecidomyiidae) - Мамаев, Б.М. (Вестник зоологии, 1973)
11 species of the genus Coquillettomyia are registered in the Palaearctic region. 5 new species are described.